Diagnostic performance of diffusion-weighted magnetic resonance imaging in assessing lymph node metastasis of esophageal cancer compared with PET - Shuto, Kiyohiko (Esophagus, 2019)
BACKGROUND: Although diffusion-weighted magnetic resonance imaging (DWI) for detecting lymph node (LN) metastasis is reported to be a successful modality for primary malignant tumors, there are few studies relating to esophageal cancer. This study aimed to clarify the diagnostic performance of DWI for assessing LN metastasis compared with positron emission tomography (PET) in patients with esophageal squamous cell cancer (eSCC). METHODS: Seventy-six patients with histologically proven eSCC who underwent curative esophagectomy without neoadjuvant treatment were reviewed retrospectively. Harvested LNs were divided into 1229 node stations with 94 metastases. Diagnostic abilities and prognostic significance were compared. RESULTS: In a station-by-station evaluation, the sensitivity was higher in DWI than PET (67% vs. 32%, P < 0.001). DWI showed more than 80% sensitivity for middle- and large-sized cancer nests and large area of cancer nests. The DWI-N0 group had a better 5-year relapse-free survival rate than the DWI-N+ group (78.5% vs. 34.2%, P < 0.001), as did the PET-N0 group. DWI-N status was an independent prognostic factor (hazard ratio [HR], 2.642; P = 0.048), as was PET-N status (HR 2.481; P = 0.033). CONCLUSIONS: DWI, which depends on cancer cell volume followed by elevated intranodal density, is a non-invasive modality and showed higher sensitivity than PET. It has clinical impact in predicting postoperative survival for patients with eSCC alongside its diagnostic ability and has significant performance in clinical practice.